KAJIAN YURIDIS DALAM ANTISIPASI KEJAHATAN CYBER - Jawade Hafidz (UNISSULA, 2014)
Cybercrime is one of the problems in Indonesia that its scope is derived from global international law. The rising rates of crime in the virtual world is influenced by factors ofcausality are difficult to obtain evidence by the action of the virtual world. When the Internetbecame accessible to everyone, they can do anything with the hunting of the target. Forexample, internet banking, hackers, search, can solve the data as amended rules becomefalse data. cybercrime is a common problem that we have to finish up with serious legalrules.In order to address the growing problem of cybercrime in Indonesia, the government makes laws and regulations specifically governing cyberlaw which were embodied as Act No. 11 of 2008 on Information and Electronic Transactions. Act No. 11 of 2008 as an effort to address cybercrime juridical and emperism, when Act No. 11 of 2008 not only addressed the issue of obscene or pornographic sites, but also establishes rules on electronic transactions is an umbrella rule of law in cyberlaw in Indonesia.